2008
DOI: 10.1073/pnas.0807743105
|View full text |Cite
|
Sign up to set email alerts
|

Memory-like CD8+and CD4+T cells cooperate to break peripheral tolerance under lymphopenic conditions

Abstract: The onset of autoimmunity in experimental rodent models and patients frequently correlates with a lymphopenic state. In this condition, the immune system has evolved compensatory homeostatic mechanisms that induce quiescent naive T cells to proliferate and differentiate into memory-like lymphocytes even in the apparent absence of antigenic stimulation. Because memory T cells have less stringent requirements for activation than naive cells, we hypothesized that autoreactive T cells that arrive to secondary lymp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
69
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(77 citation statements)
references
References 49 publications
7
69
0
1
Order By: Relevance
“…Bar graphs are mean 6 SEM. lymphopenic hosts can cause autoimmunity (16,17), precipitate allograft rejection, and prevent tolerance induction (18)(19)(20)(21)(22). In these situations, concomitant NK and T cell depletion is detrimental to allograft survival as shown in our experiments.…”
Section: Ragmentioning
confidence: 70%
See 1 more Smart Citation
“…Bar graphs are mean 6 SEM. lymphopenic hosts can cause autoimmunity (16,17), precipitate allograft rejection, and prevent tolerance induction (18)(19)(20)(21)(22). In these situations, concomitant NK and T cell depletion is detrimental to allograft survival as shown in our experiments.…”
Section: Ragmentioning
confidence: 70%
“…A characteristic feature of homeostatic proliferation is the rapid generation of functional memory T cells from naive lymphocytes in the absence of cognate antigenic stimulation (8)(9)(10)(11)(12). Although beneficial to the host by providing immunity against infections and tumors (13-15), homeostatically generated memory T cells can cause autoimmunity (16,17) and, in the setting of organ transplantation, precipitate allograft rejection and resist tolerance induction (18)(19)(20)(21)(22). Therefore, understanding the mechanisms that regulate homeostatic T cell proliferation is essential for avoiding the unwanted consequences of lymphodepletion.…”
mentioning
confidence: 99%
“…However, it is not known whether the expansion of potentially autoreactive T cells is itself sufficient to induce autoimmunity under lymphopenic conditions or whether other mechanisms are also required. (76,77). Tregs play an important role in suppressing preexisting autoreactive T cells and also control the LIP of other T cell subsets to prevent the generation of autoreactive T cell clones (78,79).…”
Section: Discussionmentioning
confidence: 99%
“…22 Recent studies have also shown a critical role for CD4 ϩ cells in breaking immune tolerance during lymphopenia, and it is possible that the lack of CD4 ϩ cells in the Rag1 Ϫ/Ϫ hosts limited the capacity to generate effective antitumor immunity. 42 Thus, profoundly lymphopenic hosts have diminished immune surveillance and an inability to generate determinant spreading during the evolution of antitumor immune responses. Furthermore, whereas the lymphopenic Rag1 Ϫ/Ϫ environment supported increased proliferation of adoptively transferred pmel-1 cells compared with cells transferred into lymphoreplete hosts, the highly proliferated cells showed diminished antigen-specific IFN-␥ production on a per-cell basis, compared with those transferred into lymphoreplete hosts ( Figure 5).…”
Section: Discussionmentioning
confidence: 99%